PENGARUH PENAMBAHAN MOLASES TERHADAP KUALITAS FISIK DAN KIMIA SILASE KULIT PISANG SEPATU (Mussa paradisiaca formatypica) - Larangahen, Arlen; Bagau, B.; Imbar, M. R.; Liwe, H. (ZOOTEC, 2017)
EFFECT OF MOLASSES ADDITION ON PHYSICO-CHEMICAL QUALITY OF BANANA PEEL (mussa paradisiaca formatypica) SILAGE. Molasses had been used previously in animal feeds. The present study was conducted to determine physical and chemical composition as affected by the addition of molasses in ensiling process of banana peels. The study was conducted for four weeks at Department of Animal and feed Science Laboratory, Faculty of Animal Husbandry, University of Sam Ratulangi, Manado. A Completely Randomized Design (CRD) arranged by 4x3 factorial with three replications was employed for analysis of varians. The two factors consisted of : A factors (level of molasses addition) were: A0=0%; A1=2%; A2=4%; and A3=6%; and B factors (incubation time) were : B1 = 14 days ; B2 = 21 days; and B3 = 28 days. Tukey’s test was used to analysis treatment differents. Variables measured were : smell, texture, color protein(%) and gross energy (Kcal/kg). The result show that the addition of molasses in ensiling process of banana peels was positively (P<0.05) interacted with incubation times, and affected on smell, crude protein, and gross energy contents, but not affected towards texture and color (P>0.05) of banana peels silage. The addition of molasses up to 6% with incubation time of 28 days gave an intermediate texture and brown color and these could be a good indication of a good or success ensiling process. The addition of molasses up to 6% with an incubation time of 21 days produced banana peels silage with protein content of 6,77% and addition of molasses up to 4% with incubation time 28 days gave gross energy of 4.390 kcal/kg. It can be concluded that addition of molasses up to 6% with incubation time 21 days produced good quality (physically and Chemically) of banana peels silage. Key words : banana peels, molasses, ensiling process, protein and gross energy content.